COMORBIDITY CONCEPTION OF SOMATIC DISEASES IN CARDIOLOGY PRACTICE - M.N. Mamedov; P. Šerpytis; V.P Podpalov; N.K Olimzoda; U.K Kamilova; V. Istrati; B.K Annaev; S.K. Mekhtiev (Interdisciplinary Approaches to Medicine, 2020)
The article review discusses the comorbidity of somatic diseases in cardiology practice. There are discussed the definition and formation history of comorbidity theory prevalence and options for the development of comorbidity. In the article also is analyzed the prevalence of comorbidity in the population and cohorts of individuals with various diseases. The commonality of risk factors for chronic non-inflectional diseases is an important prerequisite for the development of comorbidity. This study considers various options for the comorbidity development. We have to apply the concept in practical health care create. We also have to create the available tools to determine the prognostic of comorbidity of somatic diseases and. In the article are presented three methods for assessing the prognosis and survival in case of comorbidity of somatic diseases. There are considered unified views on the tactics of treatments, prevention of comorbidity and high risk of complications. At the moment the data is being accumulated on the benefits of poly pills tactics treatment. However, studies with firm endpoints are few in number to date. We have to combine the medicine with different mechanisms of action that have an evidence base for achieving target levels of individual indicators requires. The authors propose algorithms for managing patients with comorbid pathology, for which they have developed schemes of actions from diagnostics to monitoring the main indicators for evaluating the effectiveness of therapeutic interventions and preventive measures.